Practices of Teaching English to Young Learners: Voices from Islamic Primary Schools - Madayani, Nany Soengkono; Adibah, Lilik (Center of Language and Cultural Studies [CLCS], 2019)
This research is aimed at finding out the design teaching English to young learners and the teachers good practice of teaching English to young learners. The descriptive qualitative research is considered to be an appropriate design of this research. The fifth grade English teachers of SDI Qurrotaa’yun Ngunut and MI Al Azhaar Bandung Tulungagung are the subjects of the study. The data were collected by conducting observation, interview, and documentation. This research revealed that the English teachers at SDI Qurrotaa’yun Ngunut and MI Al Azhaar Bandung did good practice in TEYL, as follow; (1) English Teachers did good preparation, (2) providing various activities in teaching-learning process, (3) making the students active in the class, (4) using various kinds of assessments, (5) creating positive language environment. In conclusion, the English teachers of SDI Qurrotaa’yun Ngunut and MI Al Azhaar Bandung already implemented the principles of good teaching English for young learners. The result of this study is beneficial for English teachers to implemented good TEYL principles in their teaching. For other researchers this research was done in Islamic school background, therefore they can conduct similar research related to the TEYL in the public schools or other backgrounds.